Study of bending deformation of layered metal-composite wall-beams of regular structure under steady-state creep conditions - Yankovskii, Andrey Petrovich (Computational Continuum Mechanics, 2016)
The problem of bending deformation is formulated for layered metal-composite wall-beams of regular structure during steady-state creep in the materials of all the layers. Equations describing the stress-strain state in a beam with different degrees of precision are obtained. Based on these equations, in special cases, the ratio of the classical theory and two variants of the Timoshenko theory are determined. A simplified version of the theory is developed for statically determinate beams. Specific calculations are carried out to evaluate at different temperatures the mechanical behavior of a double-seat deep beam consisting of two types of metal-composites: regularly alternating copper and steel layers, and alternating aluminum and steel layers. It is shown that, in the case of metal-composites copper/steel, neither the classical theory nor the first variant of the Timoshenko theory guarantee the reliability of the results for the compliance of the structure even within 20% accuracy considered acceptable to study the mechanical behavior of structural elements under creep conditions. It is found that with increasing temperature the accuracy of calculations according to traditional theories decreases, and for this type of metal composites even the second variant of the Timoshenko theory does not guarantee the required accuracy at elevated temperatures. Calculations of composite beams made of aluminum and steel show that, in comparison with standard simulations, the classical theory and both versions of the Timoshenko theory significantly reduce the ductility and stress-strain state in such wall-beams under steady-state creep conditions.
Keywords: metal-composites; layered wall-beams; regular structure; steady-state creep; Timoshenko theory; Bernoulli theory; improved theory of bending